2017
DOI: 10.1016/j.lcsi.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Contributions and silence in academic talk: Exploring learner experiences of dialogic interaction

Abstract: The benefits of dialogic interaction which engenders academic talk are greater understanding of concepts and ultimately higher educational standards. However, recent research suggests students, both home and international, face certain challenges in contributing to dialogic interaction in a higher education context. This article reports on a study which explored learner experiences of dialogic interaction and reasons for contributing or remaining silent. Data were gathered from a one-semester postgraduate modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 31 publications
1
15
0
1
Order By: Relevance
“…Rather than actively contributing in cognitive interaction, these individuals may become disengaged or simply listen to more capable students, especially when the task is difficult. Engin (2017) and Rocksén (2017) suggested that confidence in knowledge can also influence individual learners' willingness to contribute. Engin (2017) added that expectations of roles can affect students' participation as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather than actively contributing in cognitive interaction, these individuals may become disengaged or simply listen to more capable students, especially when the task is difficult. Engin (2017) and Rocksén (2017) suggested that confidence in knowledge can also influence individual learners' willingness to contribute. Engin (2017) added that expectations of roles can affect students' participation as well.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies suggest that group members' participation in social interaction and the types of their interaction during collaborative learning are related; for example, groups in which students participate more jointly also tend to show more positive socio-emotional interactions and higherquality cognitive interactions (Barron, 2003;Sinha et al, 2015). However, studies have rarely addressed the fact that social interaction in collaborative learning is not static: the degree of group members' participation in social interaction during collaborative learning can fluctuate (Engin, 2017;Määttä, Järvenoja, & Järvelä, 2012;Rocksén, 2017) and their engagement in cognitive and socio-emotional interactions can vary from moment to moment .…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of literature in both higher education research generally and applied linguistics has identified considerable challenges students face in participating in spoken discourse in their disciplinary studies. Reasons for these difficulties have been reported as lack of linguistic resources, an increased cognitive load, and lack of familiarity with participation structures and routines of interaction (Engin 2017). Part of this relates to students' awareness and understanding of specialist disciplinary terminology, which is often tacit and assumed by disciplinary tutors (Bond 2020), yet key to learning content (Basturkmen 2018).…”
Section: Academic Speaking Skills In Emimentioning
confidence: 99%
“…A focus on oracy is timely as academic speaking plays a role in negotiation of meaning in learning (Mauranen 2012) as well as demonstrating understanding of the discipline (Arkoudis and Doughney 2014). In a dialogic classroom, speaking activities can become 'high stakes' and students may be reluctant to participate for a number of sociocultural and linguistic reasons (Engin 2017;Mack 2012).…”
Section: Introductionmentioning
confidence: 99%